Utveckling av tjänsteproduktivitet inom hälso- och sjukvård - Nordgren, Lars (Socialmedicinsk tidskrift, 2008)
Eftersom sjukvården saknar incitament och system för matchning av kapacitet mellan olika vårdgivare och för samordning av vårdepisoder uppstår en svår och osäker kapacitetsstyrning. Långa väntetider och ledtider mellan insatser i vården innebär också ökade risker för patienten. De bidrar även till att kapacitet och kompetenstid utnyttjas ineffektivt. Den bristande matchningen av vård medför att potentialer inte utnyttjas fullt. Organiseringen av främst sjukhusvården kan liknas vid en byråkrati som inte har anpassat sin arbetsorganisation för att kunna ta ett helhetsansvar för patientens vårdförlopp. Det saknas agentskap som samordnar vårdresurser till förmån för patienten. Det traditionella industriella produktivitetsbegreppet problematiseras, då det begreppet ses som missvisande för hälso- och sjukvård. Den dubbla problematiken bildar utgångspunkt för skissering av möjligheter att beskriva och utveckla en tentativ modell för tjänsteproduktivitet anpassad för sjukvårdens behov. Skisseringen görs med stöd av service management-skolan (tjänsteproduktivitet och värdeskapande), yield management-metoden och agentperspektivet. Vidare skisseras ett matchningssystem för att bättre matcha tillgänglig kapacitet i och mellan sjukvårdsenheter i syfte att eliminera vårdköer. As healthcare lacks incentives and systems for matching capacity between various care providers and for coordinating episodes of care, the result is capacity management that is both difficult and uncertain. Long waiting and lead times between healthcare efforts also entail increased risks for the patient. They also contribute towards capacity and expertise being utilized inefficiently. This defective matching of care means that potentials are not fully being utilized. The organising of hospital care, primarily, can be likened to a bureaucracy which has not adapted its organization of work in order to be able to assume the overall responsibility for the process of patient care. There is a lack of agentship in coordinating care resources for the benefit of the patient. The traditional industrial productivity concept which was used in manufacturing industry is problematized in this text as that productivity concept is seen as misleading for healthcare. This double set of problems forms the departure point for outlining the possibilities of describing and developing a tentative model for service productivity which is adapted to the needs of healthcare. Outlining is achieved with the support of the service management school (service productivity and value creation), the yield management method, and the agent perspective. Additionally, a matching system is outlined in order to better match the available capacity both in and between healthcare units, with the aim of eliminating queues. Keywords: Service productivity, value creation, matching, yield management, agentship